Digitalization and Early Internationalization : Systematic Literature Review Analyses - Appiah, Emmanuel; Gabrielsson, Peter (University of Hawai'i at Manoa, 2023)
Substantial anecdotal evidence has been garnered to make it uncontentious to concede to studies that stress on the influence of digital technology on early internationalization of firms. Having an interest to study how studies on this phenomenon has progressed overtime. The present paper systematically evaluates internationalization literature in which issues of digitalization feature as a component underlying the causes, processes, and outcomes of early internationalization. This enables us to outline the development of major research areas in terms of themes, theoretical and methodological approaches. We contribute by proposing several future research directions.
Keywords: Global Digital Business; born global; early internationalization; international new venture; digitalisation; digital technology; fi=Kansainvälinen liiketoiminta|en=International Business|